PENGGUNAAN KOMUNIKASI NONVERBAL DALAM PERKAWINAN CAMPURAN - Dina Dewita Bi'an, (2021)
The practice of mixed marriages between Indonesian citizens and foreigners is increasingly widespread not only with Europeans but also from various parts of the world. The difference between the colonial era and the current global era lies in how they met. Over time, technological advances are able to blur the boundaries of distance. Communicating between cities or even between continents is no longer an obstacle. The presence of the internet followed by the emergence of various social media such as Facebook, Instagram or online dating applications has made the human reach wider to socialize and interact with other people who are far away. In mixed marriages the couple comes from two different cultural backgrounds, communication that taking place between them is called cross-cultural communication. Cross-cultural communication use of message codes both verbal and nonverbal that naturally used in every interaction process. Keywords: Mixed marriages, nonverbal communication, cross-cultural communication